PREDICTION OF RISK OF FALL IN COMMUNITY-DWELLING ELDERLY POPULATION-A SURVEY - REEMA JOSHI; MANISHA RATHI; TUSHAR J.PALEKAR; SWAPNALI SADHALE (International Journal of Pharma and Bio Sciences, 2016)
Balance is a serious day to day problem in elderly people. Time up and go test and Forward reach test can be used to screen the elderly people for the risk of fall. “Time up and go test” has good interrater reliability (icc-0.98-0.99) and intra- rater reliability (0.97-0.98) and “Forward reach test” also has at inter- rater reliability i.e (icc-0.97). The present study aimed to find out the risk of fall in elderly and which age group is involved more.100 Subjects were selected randomly with 50 males and 50 females as per the criteria. Subjects between the age group of 60-80 years, both male and female were included. Clinical history of patient was taken, then procedure was explained and performed for Time Up and Go Test and Forward Reach Test .On comparison between male and female, chi square test shows Time Up And Go test p= 0.522Forward Reach Test where p = 0.018 which is significant shows female were more inclined to risk of fall than male.The study concluded that as per Time Up And Go Test and Forward Reach Test females were more under the risk of fall than males.